Membangun Kinerja Unggul: Peran Budaya dan Komitmen Organisasi di Kantor Imigrasi Kelas I Khusus TPI Surabaya - Habbi Firlana; Hanin Jauza Rahman (STISIP Widyapuri Mandiri Sukabumi, 2024)
This study aims to analyze the simultaneous influence of organizational culture and organizational commitment on employee performance at the Immigration Office Class I Special TPI Surabaya, as well as to understand how employees' perceptions of organizational culture and commitment contribute to their performance. The research uses a mix method sequential explanatory approach, combining quantitative surveys of 152 employees with qualitative semi-structured interviews. The results show that organizational culture and organizational commitment simultaneously have a significant effect on employee performance, contributing 87,2% to performance variation. Partially, a strong organizational culture, particularly in terms of employee involvement and adaptability, positively impacts performance improvement. Employees with affective commitment demonstrate higher performance, while those with continuance commitment tend to show lower performance. These findings are reinforced by qualitative insights, where employees who feel involved in decision-making and have an emotional attachment to the organization exhibit higher motivation and performance. In conclusion, strengthening organizational culture and enhancing affective commitment are key strategies for improving employee performance.